2018
DOI: 10.1021/acs.jafc.7b04768
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Metabolite Variations in Tea (Camellia sinensis L.) Leaves Grown Under Various Shade Conditions Revisited: A Metabolomics Study

Abstract: With the increase of tea (Camellia sinensis) consumption, its chemical or metabolite compositions play a crucial role in the determination of tea quality. In general, metabolite compositions of fresh tea leaves including shoots depend on plucking seasons and tea cultivators. Therefore, choosing a specific plucking time of tea leaves can provide use-specified tea products. Artificial control of tea growing, typically shade treatments, can lead to significant changes of the tea metabolite compositions. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 37 publications
5
50
0
Order By: Relevance
“…3D and 3E), concurrently with accumulation of sucrose in roots and leaves (Figs. 7 and S7), as also described in fresh tea ( C. sinensis L.) leaves grown under various shade conditions [35]. These results strongly suggest that levels of ginsenoside compounds in ginseng roots depend on their developments closely linked to seasonal climatic conditions such as sun exposure time and rainfall.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…3D and 3E), concurrently with accumulation of sucrose in roots and leaves (Figs. 7 and S7), as also described in fresh tea ( C. sinensis L.) leaves grown under various shade conditions [35]. These results strongly suggest that levels of ginsenoside compounds in ginseng roots depend on their developments closely linked to seasonal climatic conditions such as sun exposure time and rainfall.…”
Section: Discussionsupporting
confidence: 71%
“…However, after May, sucrose levels in main and lateral roots were accumulated until September, although such accumulation was not marked. In our previous study, marked accumulation of sucrose has been observed in tea ( Camellia sinensis ) leaves grown under shade or dark conditions because of lack of photosynthesis [35]. In the present study, total sun exposure time started to decrease, whereas total rainfall increased in May (Figs.…”
Section: Discussionsupporting
confidence: 64%
“…In this traditional cultivation method, tea trees are covered with shading nets when new shoots emerge, and they are grown under the shade before being harvested after between 14 and 30 days. During this period, the contents of chlorophylls (Chls) and free amino acids including theanine are increased, and that of catechins is decreased, in the tea shoot [6][7][8][9][10][11]. Tea trees usually produce new shoots thrice in a year from spring to fall in Japanese tea plantations.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics has already unveiled the metabolic profiles of tea leaves (C. sinensis), which were perturbed according to several factors, including plucking positions and seasons, climates, cultivation conditions, and cultivars [11,13,14,22,23]. However, information about the global metabolite differences between tea leaves according to the age of tea plants is very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic approaches have been reported as useful and promising tools to examine the changes in global metabolites of tea plants and potentially provide a better physiological understanding of the biochemical and cellular events [11,12]. For instance, a recent proton nuclear magnetic resonance ( 1 H NMR) based global metabolic profiling study with green tea demonstrated that the tea metabolome was clearly dependent on growing area and hence was influenced by climatic conditions [13].…”
Section: Introductionmentioning
confidence: 99%